Exploring the World of Numeracy: An Analysis of Third-Grade Elementary School Students - Rediani, Ni Nyoman (International Journal of Elementary Education, 2024)
Numeracy literacy is a crucial skill that students must master, as strong numeracy skills can support other forms of literacy. However, in some regions, numeracy skills are still at a relatively low level. This is the reason behind conducting research aimed at assessing the numeracy literacy skills of third-grade students in elementary schools. This research is of a quantitative descriptive nature, involving a sample of 32 subjects. Data collection methods include interviews, observations, and tests. The interactive data analysis model consists of three main steps: data reduction, data presentation, and drawing conclusions (verification). The research results indicate that students' numeracy literacy skills are in the low category. This is evident from the calculated scores of each student. The study also identifies, among the six components of numeracy literacy measured in this research, that the indicator requiring the most attention is the use of measurement tools, including topics such as length, time, area, and others. This condition is supported by findings from other methods, which reveal that teachers have relatively low awareness when it comes to using concrete teaching materials. This is one of the factors contributing to the low level of numeracy literacy skills.